Review of Software Fault-Tolerance Methods for Reliability Enhancement of Real-Time Software Systems - Anjushi Verma; Ankur Ghartaan; Tirthankar Gayen (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Real time systems are those systems which must guarantee to response correctly within strict time constraint or within deadline. Failures can arise from both functional errors as well as timing bugs. Hence, it is necessary to provide temporal correctness of programs used in real time applications in addition to providing functional correctness. Although, there are several researches concerned with achieving fault tolerance in the presence of various functional and operational errors but many of them did not address the problem concerned with the timing bugs which is an important issue in real time systems. As for real time systems, many times it becomes a necessity for a given service to be delivered within the specified time deadline. Therefore, this paper reviews the existing approaches from the perspective of  real time systems to analyse the shortcomings of these approaches to  present a versatile and cost effective approach in the presence of timing bugs for providing fault tolerance to enhance the reliability of the real time software applications.